Efecto de la dieta sobre la actividad metabolica de la mucosa ruminal in vitro de bovinos - Ruiz, R.=700 1 Hernandez, M.
(Es, En)
Ilus., 36 ref.
Keywords: GANADO BOVINO; DIETA; MIEL; UREA; METABOLISMO; MEMBRANA MUCOSA; RUMEN; CUBA; REVISTA CUBANA DE CIENCIA AGRICOLA